2012
DOI: 10.1007/s00276-012-1011-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medial tibial torsion on the sagittal alignment of lower legs in patients with medial knee osteoarthritis

Abstract: The angle between FA and MA in the sagittal plane increased in patients with large medial tibial torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results of this study indicated that a large tibial torsion might associated with tibial alignment. This is consistent with the findings of Takahashi et al [8]; however, they focused on the association between tibial and fibular alignment in the sagittal position and the torsion measurement was based on the tibial medial-lateral axis in the axial plane of the CT. During surgery, tibial torsion is usually applied along the anteroposterior torsion line (i.e., the line connecting the medial one-third of the tibial tubercle to the posterior cruciate ligament in the axial plane). We used the axial torsion line for localization in the same manner as we use in surgery; therefore, our results are much closer to those achieved in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study indicated that a large tibial torsion might associated with tibial alignment. This is consistent with the findings of Takahashi et al [8]; however, they focused on the association between tibial and fibular alignment in the sagittal position and the torsion measurement was based on the tibial medial-lateral axis in the axial plane of the CT. During surgery, tibial torsion is usually applied along the anteroposterior torsion line (i.e., the line connecting the medial one-third of the tibial tubercle to the posterior cruciate ligament in the axial plane). We used the axial torsion line for localization in the same manner as we use in surgery; therefore, our results are much closer to those achieved in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the strict use of extramedullary systems during surgery, there still remain some patients with poor tibial alignment. Current studies of tibial torsion generally use the transverse diameter of the tibial plateau as the transtibial axis, which we called as traditional method [810]. However, this method is not in accordance with clinical practice: the line that connects the medial one-third of the tibial tubercle and the posterior cruciate ligament are used to determine proximal tibial torsion and to confirm proximal position of the extramedullary rod, instead of the transtibial axis, during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, previous studies reported that the varus with medial knee OA was associated not only with a deformity of the shank on the frontal plane, but also with an alignment change on the horizontal plane [11,12]. In an analysis of knee OA using computed tomography images, the varus of OA knees rotated excessively outward as the varus deformity increased [13].…”
Section: Introductionmentioning
confidence: 95%